PEMBERDAYAAN MASYARAKAT MELALUI POKDARWIS DAN LITERASI DIGITAL UNTUK PENGEMBANGAN WISATA JORONG KUOK KABUPATEN AGAM - Yudhi Andoni; Alex Darmawan; Yenny Narny (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2025)
Community-based tourism development offers a sustainable approach to social and economic transformation, particularly in rural areas rich in cultural and historical potential. However, many communities, such as Jorong Kuok III Koto in Nagari Matua Mudiak, face challenges such as limited awareness of local potential and insufficient technical skills to manage and utilize these resources. Addressing this issue, the Community Service Program (PKM) titled